Dakwah Bil Hal Aisyiyah Cabang Medan Area dalam Pemberdayaan Perempuan - Nini Oktavia; Abdullah Abdullah (Syntax Corporation, 2023)
This study aims to explain about: Communication strategy of da'wah bil hal 'Aisyiyah in women's empowerment, which analyzes the inhibiting and supporting factors of da'wah bil hal 'Aisyiyah in forming an Islamic person. This research uses a qualitative approach, which is a type of research whose findings are not obtained through statistical procedures or other forms of calculation and aims to reveal phenomena holistically, contextually through data collection and natural settings and utilizing researchers as key instruments, This research data is obtained through interviews and observations. The results of the study revealed that the management of Aisyiyah Medan Area conducts: 1) caring for orphans, the poor every year, 2) doing mutual assistance, 3) each member is obliged to care for and be cared for, 4) fostering Nasyiatul Aisyah's children, 5) and contributing in the form of organizational management, 6) fostering and implementing the improvement of women's quality of life and protection of women's rights